Cannabis Intoxication, a Neglected Cause of Altered Level of Consciousness in Children: A Case Series - Mari, Alessandra; Gianolio, Laura; Abbattista, Luisa; Ripoli, Francesca; Calcaterra, Valeria; Fabiano, Valentina (International Journal of Pediatrics and Child Health, 2021)
Altered level of consciousness (ALC) represents a neurological emergency, which demands a methodical approach to evaluation and treatment. Emergency departments’ Paediatricians dealing with children with ALC need a rapid and reliable diagnostic process to rule out life-threatening conditions. ALC can be caused by structural and non-structural conditions, and, among non-structural conditions, intoxications must always be investigated. Toddlers and young children exposed to cannabis may present ALC due to explorative ingestion of the substance. We report three cases of toddlers who were admitted to our emergency department over a 12-month period with ALC due to cannabis intoxication. The three cases highlight how clinical presentation of cannabis intoxication can be variegated. Therefore, in case of afebrile children presenting with ALC Cannabis intoxication must be suspected and a urine drug test should be performed.